THE IMPACT OF CITARUM HULU DIVERSION CHANNELS ON SEDIMENT TRANSPORT AND RIVER MORPHOLOGY - Rizki Suwarno, Pravira
Flood Control of Upper Citarum River in certain eras, before 1990 to early 2000 was done by building diversion channels in the bend/ meander of the river flow. There have been more than dozens of diversion channels along the Upper Citarum River. The diversion channels’ performance in flood control is not completed thoroughly, so there are still annual floods in permanently affected areas such as Sapan, Dayeuhkolot, Baleendah, and surrounding areas. And even cause a follow-up effect on the acceleration of sediment transport and morphological changes, both in diversion channels and inlet and outlet of diversion channels. The cross-sectional analysis of the diversion channels showed that the diversion channels increase the discharge capacity of the river flow by approximately 25% or from 450 m3/s - 575 m3/s, while morphological changes range from 103.2 - 145.9% especially on the width of the riverbed. Research of meander’s radius resulted that the radius were still below the stable radius formulated by Ripley (1927). The calculation with the bankfull flood discharges obtained the outer meander’s radius have range from 600 – 1,300 meters, while the radius of the existing outer meander’s radius have range from 80- 300 meters, so it is possible that diversion channels will move towards the original bends/meanders, within tens to hundreds of years. To prevent the shifting of those channels, it is necessary to protect the walls using retaining walls, such as a reinforced concrete slab. Cliff reinforcement on the walls of the diversion channel’s inlets and outlets is also recommended Analysis of sediment transport from the effect of accelerated flow in the diversion channels that modeled with HEC-RAS provided sediment transport rates of 118,040 tons/year, causing morphological changes, erosion and sedimentation. The largest erosion was 1 meter and the largest sedimentation was 1,4 meter. Diversion channels leave the land between meander and the diversion channels or known as oxbows. Several oxbows are not well managed. Those oxbows are potentially to be used as a local drainage retention ponds and groundwater conservation. If the retention ponds are constructed with 6 (six) meters depth, similar as the Andir Retention Pond, it will have a storage capacity of 45,000 – 645,000 m3, with a total storage of 2.9 million m3, which can be used as raw water locally with the local Water Treatment Plant (WTP). Retention ponds also serve as an artificial recharge of groundwater. It was analyzed from the changes on the coefficient of surface soil permeability from 10-6 - 10-5 cm/s to 10-5 - 10-3 cm/s, equivalent to a recharge value of 86.4 mm/day that exceeds normal rainfall (>60 mm/day).